2021
DOI: 10.1002/cssc.202101873
|View full text |Cite
|
Sign up to set email alerts
|

Quasi‐Parallel NiFe Layered Double Hydroxide Nanosheet Arrays for Large‐Current‐Density Oxygen Evolution Electrocatalysis

Abstract: Designing advanced electrocatalysts for oxygen evolution at large current density (>500 mA cm−2) is critical to practical water splitting applications. Herein, a novel quasi‐parallel NiFe layered double hydroxide (NiFe LDH) nanosheet arrays with pattern alignment on Ni foam was developed. The initial α‐Ni(OH)2 layer induced effective coprecipitation between Ni2+ and Fe3+ for the formation of LDH phase, guaranteeing the electronic pulling effect among metal cations and enhancing the interaction between active m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…[5] Ye et al prepared a novel quasi-parallel NiFe LDH nanosheet array to enhance the electronic traction effect among metal cations and the interaction between the active materials and substrate for excellent adhesion and conductivity, endowing the nanosheet with outstanding oxygen evolution activity and stability. [6] Beyond the control of crystallinity, heteroatom doping is an available strategy to modulate the electronic structure of electrocatalysts. Tang et al reported that the rich in-plane active sites can be generated by the lattice-confined Mo atoms to activate the basal plane of Mo-CoOOH with three-dimensional (3D) nanoframes, where the lattice-confined Mo sites in the two dimensional (2D) basal-plane are active sites for OER, which can bond moderately with the reaction intermediates and thereby enhance the activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5] Ye et al prepared a novel quasi-parallel NiFe LDH nanosheet array to enhance the electronic traction effect among metal cations and the interaction between the active materials and substrate for excellent adhesion and conductivity, endowing the nanosheet with outstanding oxygen evolution activity and stability. [6] Beyond the control of crystallinity, heteroatom doping is an available strategy to modulate the electronic structure of electrocatalysts. Tang et al reported that the rich in-plane active sites can be generated by the lattice-confined Mo atoms to activate the basal plane of Mo-CoOOH with three-dimensional (3D) nanoframes, where the lattice-confined Mo sites in the two dimensional (2D) basal-plane are active sites for OER, which can bond moderately with the reaction intermediates and thereby enhance the activity.…”
Section: Introductionmentioning
confidence: 99%
“…Ye et al. prepared a novel quasi‐parallel NiFe LDH nanosheet array to enhance the electronic traction effect among metal cations and the interaction between the active materials and substrate for excellent adhesion and conductivity, endowing the nanosheet with outstanding oxygen evolution activity and stability [6] . Beyond the control of crystallinity, heteroatom doping is an available strategy to modulate the electronic structure of electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the Tafel results in Figure S4b show that the most active Ni/Ni 3 Se 2 sample has the smallest Tafel slope (114 mV dec À 1 ), indicating that the sample has fast kinetics during the OER process. [20] These results indicate that appropriate metallic nickel content can effectively improve the electrocatalytic performance of the nickel-nickel selenide composite.…”
Section: Resultsmentioning
confidence: 85%
“…Current density was calculated based on the geometric area of electrodes. At different scan rates (20,40,60,80,100, 120 and 140 mV s À 1 ), the capacitances of samples were obtained by CVs in the non-Faradaic potential region. The working electrode was prepared through a drop-casting method and the typical procedure was as follows: a catalyst ink was prepared by dispersing 4 mg of the sample powder in 1 mL of waterÀ ethanol solution at volume ratio of 2 : 1 containing 30 μL of Nafion solution.…”
Section: Electrocatalytic Water Oxidationmentioning
confidence: 99%
“…The formation of the parallel layer is probably by the formation of tiny grooves when KMnO 4 corrodes Ni(OH) 2 . [ 43 ] The formation of such parallel sheets can expose more active edge sites, which could supply more adsorption and reactive sites to enhance the sensing performance. However, the thickness of the NiO nanosheets decreased to approximately 8.9 nm.…”
Section: Resultsmentioning
confidence: 99%